2005
DOI: 10.1523/jneurosci.0252-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by Spinal μ- and δ-Opioid Agonists of Afferent-Evoked Substance P Release

Abstract: Opioid -and ␦-receptors are present on the central terminals of primary afferents, where they are thought to inhibit neurotransmitter release. This mechanism may mediate analgesia produced by spinal opiates; however, when they used neurokinin 1 receptor (NK1R) internalization as an indicator of substance P release, Trafton et al. (1999) noted that this evoked internalization was altered only modestly by morphine delivered intrathecally at spinal cord segment S1-S2. We reexamined this issue by studying the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
112
1
5

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(128 citation statements)
references
References 62 publications
10
112
1
5
Order By: Relevance
“…Consistent with a putative release of opioid peptides, ENK-ir interneurons are in close proximity of clusters of MOR-ir nociceptive neurons (Arvidsson et al, 1995) whose activation may contribute to presynaptic inhibition of sensory neuron neurotransmitter release (Kondo et al, 2005) and/or postsynaptic hyperpolarization of excitatory neurons (Trafton et al, 2000). Interestingly, i.t.…”
Section: Opioid-mediated Inhibition Of Inflammatory Pain Following Imentioning
confidence: 81%
“…Consistent with a putative release of opioid peptides, ENK-ir interneurons are in close proximity of clusters of MOR-ir nociceptive neurons (Arvidsson et al, 1995) whose activation may contribute to presynaptic inhibition of sensory neuron neurotransmitter release (Kondo et al, 2005) and/or postsynaptic hyperpolarization of excitatory neurons (Trafton et al, 2000). Interestingly, i.t.…”
Section: Opioid-mediated Inhibition Of Inflammatory Pain Following Imentioning
confidence: 81%
“…It has been shown that the release of glutamate and substance P from primary afferent neurons is inhibited by δ-opioid agonists (Glaum et al, 1994;Kohno et al, 1999;Kondo et al, 2005). Thus, the presynaptic action of δ-opioid agonists on nociceptive afferent terminals has been considered an important mechanism underlying the spinal analgesic effect of δ-opioid agonists.…”
Section: Discussionmentioning
confidence: 99%
“…A prominent example is the inhibition of substance P and calcitonin gene-related peptide (CGRP) release (both are pronociceptive and proinflammatory neuropeptides) from central and peripheral terminals of primary afferent neurons ( Fig. 1) (Yaksh, 1988;Khasabova et al, 2004;Kondo et al, 2005). At the postsynaptic membrane, opioid receptors mediate hyperpolarization by opening G protein-coupled inwardly rectifying K ϩ (GIRK) channels, thereby preventing neuronal excitation and/or propagation of action potentials for review, see Lü scher and Slesinger, 2010).…”
Section: Opioid Receptormentioning
confidence: 99%